Peningkatan Pengetahuan Melalui Seminar Awareness Tentang Penanggulangan HIV di Tempat Kerja - Harjono, Afrian Eskartya; Jihan Faradisha; Rici Riansyah; Rizqy Kartika Sari (Universitas Alifah Padang, 2024)
Human Immunodeficiency Virus (HIV) is a virus that damages the immune system and weakens the body's ability to fight various types of diseases. If HIV is not treated, it can advance to the greater stage called Acquired Immuno-Deficiency Syndrome (AIDS). The highest percentage of HIV infections is reported in the age group of 25-49. Meanwhile, people age 30-39 are the highest percentage of AIDS. Therefore, HIV/AIDS can pose a threat to workers in Indonesia, impacting the economy and causing issues within a company. Conference is conducted in order to increase knowledge of HIV Awareness at the workplace with 22 participants. The participants are expected to gain a knowledge about HIV transmission and HIV prevention at the workplace. The effectiveness level of the conference awareness is proven by pre-test and post-test. Pre-test showed that 8 participants answered correctly on the HIV transmission aspect, and 11 participants answered correctly on the HIV prevention aspect. Post test was conducted after the speaker deliver the material to the participants. The results are 15 participants answered correctly on the HIV transmission aspect, and 14 participants answered correctly on the HIV prevention aspect. The increased of knowledge after awareness conference on HIV transmission aspect showed 32% and HIV prevention aspect 14%. It can be concluded that the conference awareness is an effective way to improve the knowledge of HIV awareness at the workplace